Perlindungan Hukum Atas Data Pribadi Nasabah Bank Pengguna Mobile Banking dalam Perspektif Uu No 27 Tahun 2022 tentang Kebocoran Data - Ema Irmawati; John Pieries; Wiwik Sri Widiarty (Syntax Corporation Indonesia, 2024)
Research Objectives: a) To find out and analyze the Legal Arrangements for Customer Personal Data Protection in banking mobile banking services are still happening to the detriment of customers. b) To find out and analyze the Bank's Responsibility for the Confidentiality of Customer Personal Data in accordance with Law no. 27 of 2022. The method applied in this legal research is the study of normative juridical research methods, which refers to substance research from laws and regulations, books, journals and papers as well as other jurisprudence. However, this research is also based on empirical research where the data is taken from field studies. As a result, the theory of legal protection and legal certainty has a close relationship in legal regulation to the protection of customer personal data in mobile banking services. Legal protection theory emphasizes the importance of protecting human rights, including the right to personal data protection. The right to personal data protection is a human right guaranteed by the Constitution of the Republic of Indonesia Year 1945 (UUD 1945) Article 28G Paragraph (1).